Infrastructural Facilities Development in Krishi Vigyan Kendras in Rajasthan-A Comparative Assessment - B.S. Meena, Baldeo Singh (Indian Journal of Extension Education, 2022)
Agriculture is the main stay of India’s economy onwhich 70 percent of total population depends directly.Role of agricultural information in the production offood grains has been always critical, becausefarmer’s are always want of new information/technical know how. In this regard Govt. of Indiaand States Government launched several transfer oftechnology programmes through which new advancesin agricultural could be conveyed to farmerseffectively.